Acute unilateral sensorineural hearing loss associated with anabolic steroids and polycythaemia: case report. Issue 3 (14th December 2015) - Tikka, T; Mistry, N; Janjua, A
Abstract: Background: Unilateral sudden sensorineural hearing loss due to an infarct in the vertebrobasilar system has been widely reported. Most patients have a background of traditional coronary risk factors related to these cerebrovascular episodes. Case report: A 32-year-old male, a regular user of anabolic steroids, presented to the emergency department with unilateral sensorineural hearing loss and symptoms suggestive of an infarct of the anterior inferior cerebellar artery but in the absence of risk factors for ischaemic stroke. Results: Magnetic resonance imaging confirmed the presence of infarction in the region supplied by the anterior inferior cerebellar artery. Polycythaemia was found on haematological analysis, which we believe was secondary to the use of anabolic steroids. The patient was commenced on aspirin as per the stroke management protocol. There was resolution of neurological symptomatology six weeks after the episode, but no improvement in hearing. Conclusion: To our knowledge, this is the first case report of unilateral sensorineural hearing loss secondary to the use of anabolic steroids causing polycythaemia. This cause should be considered in the differential diagnosis of patients presenting with sensorineural hearing loss, especially in young males, when no other risk factors can be identified.